Chemistry - Housecroft, Catherine E. (Addison Wesley Longman, 1997)
A welcomed, exciting text which integrates the physical, organic and inorganic components of chemistry. It is supported with stimulating and thought-provoking examples, which demonstrate to students, early on in their career, the overlaps and connections between these areas